Fetal Heart Monitoring Prior to Cesarean Birth. Issue 3 (May 2015) - Wisner, Kirsten
<x xml:space="preserve">Abstract</x> What is recommended for fetal assessment prior to cesarean birth? Do all women need continuous electronic fetal monitoring?